2009
DOI: 10.1016/s0079-6123(09)17711-7
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness and epilepsy: why are complex-partial seizures complex?

Abstract: Why do complex-partial seizures in temporal lobe epilepsy (TLE) cause a loss of consciousness? Abnormal function of the medial temporal lobe is expected to cause memory loss, but it is unclear why profoundly impaired consciousness is so common in temporal lobe seizures. Recent exciting advances in behavioral, electrophysiological, and neuroimaging techniques spanning both human patients and animal models may allow new insights into this old question. While behavioral automatisms are often associated with dimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 157 publications
1
64
0
1
Order By: Relevance
“…Furthermore, symptoms associated with epileptic EEG alterations in animals may be so subtle that they are not easily recognized. Examples are behavioral arrest, increased whisker twitching and chewing, and stereotyped behaviors, such as exploration, grooming, and scratching, which can represent the only symptoms of limbic seizures in rodents 27, 28. Furthermore, paroxysmal events in the hippocampus, as described in the present study, may induce a memory lapse that cannot be easily detected in an animal 22…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, symptoms associated with epileptic EEG alterations in animals may be so subtle that they are not easily recognized. Examples are behavioral arrest, increased whisker twitching and chewing, and stereotyped behaviors, such as exploration, grooming, and scratching, which can represent the only symptoms of limbic seizures in rodents 27, 28. Furthermore, paroxysmal events in the hippocampus, as described in the present study, may induce a memory lapse that cannot be easily detected in an animal 22…”
Section: Discussionmentioning
confidence: 52%
“…The recent development of an animal model has shed additional light on the mechanisms by which focal temporal lobe seizures cause loss of consciousness via long-range disruption by subcortical activating systems of neocortex [23][24][25]. In particular, fMRI decreases were found in the orbital frontal, anterior cingulate, and posterior cingulate cortex / retrosplenial cortex during seizures similar to changes observed in human patients.…”
Section: Default Mode Network Involvement In Complex Partial Seizuresmentioning
confidence: 74%
“…3) [8,13,57]. For temporal lobe epilepsy, it seems that loss of consciousness occurs by seizure activity arising from the temporal lobe and propagating to subcortical structures; this may inhibit the arousal functions of the thalamus, basal forebrain and upper brainstem, to widely deactivate frontal and parietal association cortex [24,71]. In contrast, temporal lobe seizures that do not cause loss of consciousness may only produce impaired activity at the seizure foci without widespread effects via propagation to midline subcortical structures, and would thus spare cortical regions including the DMN.…”
Section: Default Mode Network Involvement In Complex Partial Seizuresmentioning
confidence: 99%
“…Recently we proposed a 8 criteria scale in order to capture the different elements for a more objective evaluation of the AOC during seizures (Table 1) [1]. Different hypothesis have been proposed to explain how those seizures could impair consciousness [20]. Intracerebral EEG recordings studies have suggested that alteration of consciousness could be related to the spread of epileptic discharge to cortical structures contralateral to the origin of the seizures and could be more frequent in seizures affecting the dominant hemisphere [31].…”
Section: No Visual Attention (0 or 1)mentioning
confidence: 99%